2018
DOI: 10.4102/hts.v74i1.4848
|View full text |Cite
|
Sign up to set email alerts
|

Circumcision and prevention of HIV and AIDS in Zimbabwe: Male genital cutting as a religio-cultural rite

Abstract: Circumcision originated from ancient religious (biblical) and cultural societies. Study has shown that in both the biblical (Israelite) context and among the Karanga people in Zimbabwe circumcision emerged as a rite of passage for a boy child’s entry into manhood. Modern societies promulgate circumcision as a preventive method against HIV and AIDS. The present study argues that circumcision tends to promote irresponsible sexual behaviour and trivialises the sacredness of sex. (1) To safeguard societies against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Therefore, traditional male circumcision procedure relies heavily on traditional medicines to Research into medicinal uses, phytochemistry and pharmacological properties of medicinal plants used to treat and manage circumcision wounds offers tremendous potential for developing new pharmaceutical health products and drugs. Although conventional medical circumcision is popular in some urban African cities as the World Health Organisation (WHO) recommended male circumcision as part of a comprehensive programme for preventing human immunodeficiency virus (HIV) transmission in areas with high endemic rates (24)(25)(26)(27)(28)(29)(30)(31), traditional male circumcision is still widely practised in Eastern and Southern Africa (1)(2)(3)(4). Studies are there (29) arguing that the emergency of HIV has brought the ancient traditional male circumcision on spot light as a result of recent studies which have demonstrated that it does not only reduce the rate of HIV infection but the ancient procedure also reduces penile cancer and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, traditional male circumcision procedure relies heavily on traditional medicines to Research into medicinal uses, phytochemistry and pharmacological properties of medicinal plants used to treat and manage circumcision wounds offers tremendous potential for developing new pharmaceutical health products and drugs. Although conventional medical circumcision is popular in some urban African cities as the World Health Organisation (WHO) recommended male circumcision as part of a comprehensive programme for preventing human immunodeficiency virus (HIV) transmission in areas with high endemic rates (24)(25)(26)(27)(28)(29)(30)(31), traditional male circumcision is still widely practised in Eastern and Southern Africa (1)(2)(3)(4). Studies are there (29) arguing that the emergency of HIV has brought the ancient traditional male circumcision on spot light as a result of recent studies which have demonstrated that it does not only reduce the rate of HIV infection but the ancient procedure also reduces penile cancer and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%